Validating and Validate the Persian Version of International Social Survey Programme - Reihaneh Mahallati (Journal of Global Pharma Technology, 2017)
The aim of this study was to validate and validate the International Social Survey Program me (ISSP) single significant pride. National pride of economy, politics, art, history of a country known to play a role in the daily lives of individuals and determine their attitude Methods: The study population all male and female high school students in regions 1 and 2 in Yazd second academic year 2014-15 number was 14069. This study was a multi-stage random sampling method. The sample size of 525 patients was estimated by Cohen's table. However, after the removal of incomplete questionnaires and remove data threw a total of 474 participants entered the data were analyzed.This questionnaire measures at both national prides. The first, ISSP in the successes especially proud that the people in the 10 areas assessed The second part of the questionnaire, measures of general national pride and includes 5 components that evaluates the patriotism and sense of national superiority. The reliability of national pride in the success and national pride, especially from 0.72 to 0.81 0.33 to 0.70 along been public Results: Confirmatory factor analysis in this study showed that the test of ISSP in the population has two components Basic pride and pride is special. Public national from 0.33 to 0.70 has been along.Keywords: Validating, International social survey program me, Persian version.